Legal Analysis of Consumer Protection in E-Commerce Transactions Based on Contract Law and Law Number 8 of 1999 on Consumer Protection - Sarles Gultom; Parlin Dony Sipayung; Yuspika Yuliana Purba; Natalia Ginting (Academic Solution Publisher, 2025)
Legal protection for consumers in electronic transactions, as regulated in Article 1 paragraph 1 of Law No. 8 of 1999 concerning Consumer Protection which states that